Cinemática do tronco, pelve, quadril e joelho durante o agachamento unipodal em mulheres com e sem dor femoropatelar: uma análise usando statistical parametric mapping - Silva, Cassius Iury Anselmo e (Universidade Federal de São Carlos, 2025)
Previous studies evaluating trunk, pelvis, hip, and knee kinematics during the single-leg squat in individuals with and without patellofemoral pain (PFP) have used discrete parameter-based analysis. This approach may not accurately represent the movement, as it limits continuous time-series data to a single time point, thereby failing to account for potential differences that might exist at other points in the movement. Although the single-leg squat has been used to assess lower limb kinematics, as it mimics cyclic movements performed in daily activities and sports, previous studies have performed the task using single, non-consecutive repetitions. This study aimed to determine whether differences exist in trunk, pelvis, hip, and knee kinematics during consecutive repetitions of the single-leg squat between women with and without PFP. We employed statistical parametric mapping (SPM), which allows for the analysis of timeseries data. Thirty women were allocated into two groups: the PFP group (n = 15, 24.7 ± 2.3 years) and control group (n = 15, 24.8 ± 3.1 years). We measured trunk, pelvis, and knee angles in the frontal plane and hip angles in the frontal and transverse planes using a three-dimensional motion analysis system. Angles were assessed during the eccentric and concentric phases of five consecutive single-leg squats. Differences between groups were analysed using one-dimensional SPM. An SPM independent t-test was used to compare pelvis angles between groups, while an alternative non-parametric test was applied to the remaining variables. The significance level was set at 5%. The PFP group exhibited greater hip internal rotation at the beginning of the eccentric phase (0–3%, p = 0.035) and at the end of the concentric phase (94– 100%, p = 0.026). There were no other significant differences between groups (p > 0.05). Our findings suggest that clinicians should incorporate strategies to control hip motion in the transverse plane during weight-bearing tasks in women with PFP.
Kinematics of the runk, pelvis, hip, and knee during unipodal squatting in women with and without patellofemoral pain: an analysis using statistical parametric mapping
Keywords: Biomecânica; Dor anterior do joelho; Lesão; Reabilitação; Biomechanics; Anterior knee pain; Injury; Rehabilitation; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL